Financial Information in Colombia - Gine, Xavier (World Bank, Washington, DC, 2017)
An audit study was conducted in Colombia following the protocols in Gine and Mazer (2017). Trained auditors visited multiple financial institutions, seeking credit and savings products. Consistent with Gabaix and Laibson (2006) and similar to Gine and Mazer (2017), the staff only provided information about the cost when asked, disclosing less than a third of the total cost voluntarily. In addition, clients were rarely offered the cheapest product, most likely because staff was incentivized to offer more expensive and thus more profitable products to the institution.